(untitled) (Delta Medical College Journal, 2017)
Background: The prevalence of gestational diabetes mellitus (GDM) is 9.7% in Bangladesh. Infants of diabetic mothers (IDM) have a significant chance to develop various complications including glucose instability. Objective: To find out the incidence of IDM among low birth weight (LBW) babies and their relation with blood glucose level during 1st 48 hours of life. Materials and method: This cross sectional study was conducted from July 2012 to June 2013 on 189 LBW babies with birth weight <2500 gram up to 1000 gram admitted within 3 hours of life in the neonatal unit of Jalalabad Ragib Rabeya Medical College Hospital, Sylhet, Bangladesh. Detailed history including maternal history of GDM was taken. Blood glucose level was done during admission and at 3 to <6 hours of age, 6 to <24 hours of age and 24-48 hours of age. Results: Among 189 cases, male baby were 136 and female baby were 53. Preterm babies were 49.2% and term babies were 50.8%. Most of the newborn babies were delivered at hospital (78.3%) and by vaginal delivery (75.1%). Among LBW babies, 5% were infants of diabetic mothers. Hypoglycemia was present in 33.3% of infants of diabetic mothers which was significantly higher than infants of non-diabetic mothers (5.6%) within 3 hours of age. Conclusion: Infants of diabetic mothers may present as LBW and may be delivered prematurely and they have high incidence of hypoglycemia during early periods of life. Delta Med Col J. Jan 2017 5(1): 4-8